Manajemen strategi di perbankan syariah: Konsep, implementasi dan tantangan - Fitroh, Ike Silvia (Maliki Interdisciplinary Journal, 2025)
Management strategy plays a crucial role in the management of Islamic banks to ensure sustainable growth, improved performance, and financial stability in line with sharia principles. This study discusses the concept of management strategy and its relationship to risk management in the Islamic banking industry in Indonesia, focusing on a case study of Bank Mandiri Syariah (BMS) and the integration process of three large Islamic banks into Bank Syariah Indonesia (BSI). The research method uses a qualitative approach through a literature review of previous research and secondary data sources. The results of the study indicate that the synergy between management strategy and risk management contributes significantly to increased competitiveness, operational efficiency, and strengthening digital service innovation. This integration not only strengthens customer trust but also ensures that all operational activities are in accordance with sharia principles. This study recommends the development of innovative strategies and optimal utilization of digital technology to improve service quality, expand market reach, and support the sustainability of the Islamic banking industry in the era of digital transformation.